2022
DOI: 10.1109/jlt.2021.3124227
|View full text |Cite
|
Sign up to set email alerts
|

Over 100 mW Stable Low-Noise Single-Frequency Ring-Cavity Fiber Laser Based on a Saturable Absorber of Bi/Er/Yb Co-Doped Silica Fiber

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In 2020, Yeh et al [20] presented a tunable single-frequency narrow linewidth fiber laser with erbium doped fiber (EDF) as SA and self-feedback injection and the wavelength tuning range was 60 nm with an average output linewidth of 18 kHz. In 2022, Wan et al [21] of Shanghai University reported a ring-cavity single-frequency fiber laser with Bi/Er/Yb co-doped fiber as the SA, and the tested linewidth was less than 7.5 kHz. In this regard, the generation of single-frequency lasers by employing the technique of using unpumped fibers as SA with linewidths below 1 kHz and a power of tens of milliwatts has yet been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Yeh et al [20] presented a tunable single-frequency narrow linewidth fiber laser with erbium doped fiber (EDF) as SA and self-feedback injection and the wavelength tuning range was 60 nm with an average output linewidth of 18 kHz. In 2022, Wan et al [21] of Shanghai University reported a ring-cavity single-frequency fiber laser with Bi/Er/Yb co-doped fiber as the SA, and the tested linewidth was less than 7.5 kHz. In this regard, the generation of single-frequency lasers by employing the technique of using unpumped fibers as SA with linewidths below 1 kHz and a power of tens of milliwatts has yet been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, near-infrared gain fiber-based fiber lasers working at around 1.0 µm have been widely used in optical detection, medical surgery, and laser ranging [1][2][3][4]. Some rare-earth ions, like Yb 3+ ions or Nd 3+ ions, have realized 1.0 µm emissions in suitable matrix materials [5][6][7][8]. Compared with Nd 3+ ions, the energy level of Yb ions is relatively simple and only possesses 2 F 5/2 and 2 F 7/2 levels [9].…”
Section: Introductionmentioning
confidence: 99%
“…Single-frequency fiber ring lasers (FRLs) have been extensively investigated owing to their applications in fiber-optic sensing, optical communication, high-precision spectroscopy and seeding of high-power fiber lasers [1][2][3]. Compared with linear-cavity lasers, most FRLs have a longer fiber ring cavity, narrower mode spacing, and lots of fiber devices incorporated in the cavity, which increase the complexity of laser configuration and make the laser performance highly susceptible to intracavity heat accumulation effect and external perturbation.…”
Section: Introductionmentioning
confidence: 99%